Negotiating Cultural Identity: Indonesian EFL Learners' Use of English to Globalize Local Narratives - Yuliani, Fitria; Poniman (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study investigates how Indonesian EFL (English as a Foreign Language) learners negotiate their cultural identity within a Cross-Cultural Understanding (CCU) course. Through a qualitative analysis of performance-based final term projects, the research explores the tension between the mandatory use of English and the students' desire to project local heritage. Data from 23 student performances reveal that learners do not merely adopt Western norms. Instead, they perform a "hybrid identity," using English as a tool to globalize local narratives.